La Main Ecological Structure at a local level. A proposal for the urban renovation of Fenicia, Las Aguas, Bogota (2014)
Based on the integration of all elements defined historically as part of Bogota´s Main Ecological Structure, such as protected areas, ecological networks and green infrastructure, the article proposes a local planning model for urban renovation projects as a design example of Bogota´s urban border renaturalization. The proposal includes planning, public green space design, and urban biodiversity management as a way to overcome the tension between contrasting and conflicting land uses.